Fabrication and microstructure of perovskite CsPbCl3 nanocrystallized chalcogenide glass‐ceramics. Issue 9 (21st May 2019) - Yu, Mingqiang; Yu, Xinlan; Long, Nengbing; Lin, Changgui
Abstract: Transparent chalcogenide glass‐ceramics containing CsPbCl3 perovskite nanocrystals were prepared through an elaborated composition design of 80GeS2 ·5Ga2 S3 ·15CsPbCl3 . Large size distribution of CsPbCl3 nanocrystals is observed ranging from 10 to 200 nm. XRD, Raman spectra, and SEM techniques were employed to study the further microstructural evolution after thermal treatment. The precipitation of PbGeS3 and GeS2, together with CsPbCl3, was identified according to the XRD patterns and Raman spectra. This work is of guiding significance for future design of cesium lead halide perovskite nanocrystals in chalcogenide glass‐ceramics.